School Size, Achievement, and Achievement Gaps - McMillen, Bradley J. (Education Policy Analysis Archives, 2004)
In order to examine the relationship between school size and achievement, a study was conducted using longitudinal achievement data from North Carolina for three separate cohorts of public school students (one elementary, one middle and one high school). Results revealed several interactions between size and student characteristics, all of which indicated that the achievement gaps typically existing between certain subgroups (i.e., more versus less-advantaged, lower versus higher-achieving) were larger in larger schools. Results varied across the grade level cohorts and across subjects, but in general effects were more common in mathematics than in reading, and were more pronounced at the high school level. Study results are discussed in the context of educational equity and cost-effectiveness.